Doppler ultrasound protocol for patients with hidradenitis suppurativa - Ariany Tomaz de Aquino Saran Denofre; Carolina Meloni Stecca; Juliana Yumi Massuda Serrano; Thais Helena Buffo; Rachel Polo Dertkigil; Renata Ferreira Magalhães (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Hidradenitis suppurativa (HS) is a chronic inflammatory disease that leads to the formation of nodules, abscesses and fistulas, with the formation of scars and fibrosis, causing significant impairment in patient quality of life. The diagnosis is clinical, using scores to classify the severity of the condition; currently the most recommended classification is the International Hidradenitis Suppurativa Severity Scoring System (IHS4). Doppler ultrasound has been used to complement the clinical evaluation of patients with HS. It is possible to observe subclinical lesions that change the staging, the severity of the case, and its treatment, either clinical or surgical. Correct treatment is essential to minimize the consequences of this disease for the patient. Objective To establish an outpatient protocol for the use of Doppler ultrasound in the care of patients with HS. Methods A narrative review of the literature was carried out on the use of Doppler ultrasound in patients with hidradenitis suppurativa; a referring protocol and technique orientations for imaging assessment in HS were created. Results Recommendation to perform ultrasound evaluation of symptomatic areas eight weeks after using antibiotics and four, 12, and 24 weeks after starting immunobiologicals; apply SOS-HS ultrasound severity classification. Study limitations The review did not cover all literature on ultrasound and HS; no systematic review was carried out, but rather a narrative one. Conclusions The correct assessment of patients staging must be carried out using dermatological ultrasound to avoid progression to scars and fibrosis, which compromise patients quality of life.